178-W picosecond green laser with active beam-pointing stabilization - Zhang, Zhendong; Bai, Zhenao; Song, Xiaoquan; Zhang, Yakai; Liang, Bo; Liu, Tingxia; Wang, Weiguo (Frontiers in Physics, 2022)
Picosecond lasers with high average power and high beam quality have been widely used for precision processing and space exploration. In this study, we report a high-power picosecond green laser using a multistage Yb-doped rod-shaped photonic crystal fiber as an amplifier combined with a beam combination. The single amplification module achieves a 1030 nm laser output of 146.8 W, and the maximum second harmonic generation (SHG) power is 92 W with a frequency conversion efficiency of 63.5%. The combined beam of the two SHGs resulted in a final output of 178 W with a repetition frequency of 24.07 MHz, pulse width of 50.1 ps, and beam quality factor of M2 = 1.16. Furthermore, an adaptive filter control method of a two-axis fast-steering mirror was applied to suppress the beam jitter to up to 45 Hz.